Territorialisering og ejendomsret. Nakskov by kontra grevinde Reventlow 1745-54 - Riisager, Niels (Historisk Tidsskrift, 2024)
Territorialization and property: The city of Nakskov vs. Countess Reventlow 1745–1754 Historians of Danish rural history have long recognized that property rights in early modern times (in Danish fællesskabstiden) were highly complicated, often with a multilayered and collective structure that differs fundamentally from the modern norm of individual and absolute rights. Less has been written on the territorialization of property, i.e., how property rights were manifested in rural space. While some scholars have pointed out a general historical connection between property rights regimes and their spatial manifestation – for instance, in the sense that the consolidation of individual property rights went hand in hand with the emergence of stronger, more clearly defined property boundaries – the relation has generally been depicted as one of simple causation. However, based on a case study of a commission (kommissionsdomstol) established to decide the case between the borough of Nakskov and Countess Ida Margrethe von Reventlow in the year 1752, the present article shows that the interrelation between the legal and spatial dimensions of property was neither historically unidirectional nor a question of simple mutual reinforcement. Thus, the two dimensions could clash, with solutions being contingent upon the success of the concrete territorialization practices of the agents involved. In this case, the borough failed to provide a territorial shape to certain property rights, resulting in an imbalance between pre-existing rights and spatial arrangements.